(untitled) (PAAN Journal, 2026)
This study examines the adaptability of ‘Batho Pele’ principles, also called ‘People First,’ of South Africa to the public service delivery in Nepal, which is experiencing a federal transition. As a developing nation, Nepal’s public service delivery is often hindered by inefficiency, a lack of transparency, and low citizen engagement. While the Constitution of Nepal promised inclusive and accountable governance, the public service remains beset by bureaucratic inertia, political instability, and structural exclusion. Drawing on qualitative interpretative literature reviews, the paper examines the Batho Pele principles of consultation, service standards, access, courtesy, information, openness, redress, and value-for-money in a contextual setting to reflect on their suitability to Nepal’s federal, culturally diverse governance landscape. According to the analysis, Batho Pele provides not only administrative mechanisms but also a normative framework for citizen-first governance, addressing Nepal’s fragmented reforms as isomorphic mimicry. The study emphasizes the importance of adaptive policy translation over wholesale or ad hoc model adoption, drawing on comparative insights from South African experiences. Finally, this study contributes to the broader discourse on policy transfer and public service innovation, offering practical recommendations for integrating Batho Pele values into Nepal’s evolving federal public administration and inclusive public service delivery framework.